Prescription trend and lactic acidosis in patients prescribed metformin before and after the revision of package insert for allowing metformin administration to patients with moderately decreased kidney function based on real-world data from MID-NET® in Japan - Waki, Takashi; Okada, Yusuke; Kinoshita, Yuki; Kajiyama, Kazuhiro; Ishiguro, Chieko; Nakazato, Yuki; Kimura, Ryota; Maniwa, Harumi; Horiuchi, Naoya; Iguchi, Toyotaka; Uyama, Yoshiaki (Frontiers in Medicine, 2024)
Introduction This study was conducted to understand the impact of package insert (PI) revision in Japan on 18 June 2019 to allow metformin use for patients with moderately decreased kidney function (30 ≤ estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m2). Methods A new user cohort design was employed to examine the prescription trend and the occurrence of lactic acidosis in patients prescribed metformin before and after PI revision using the Medical Information Database Network (MID-NET®). Results From 12 May 2016 to 31 March 2020, 5,874 patients (before, n = 4,702; after, n = 1,172) were identified as new metformin users, including 1,145 patients (before, n = 914; after, n = 231) with moderately decreased kidney function. Although no marked changes in metformin prescription were observed before and after PI revision, the daily metformin dose at the first prescription decreased after PI revision. For both before and after PI revision, less than 10 cases of lactic acidosis occurred in all patients prescribed metformin, and no lactic acidosis was observed in patients with moderately decreased kidney function. Conclusion The results of this study are useful for understanding the safety of metformin use in patients with decreased kidney function and suggest no worse impacts of PI revision in Japan, indicating no further safety concerns on metformin use in patients with moderately decreased kidney function under the situation with careful use and safety monitoring of metformin.